Employee Commitment and Organizational Policies at PT PLN (Persero) UP3 Surakarta - Anton Agus Setyawan; Dea Pradita Kumalasari (Universitas Muhammadiyah Yogyakarta, 2023)
PT. PLN represents one of BUMN's moving in the field of ready electric power which it's existence is very required by society. Thereby PT. PLN claimed to provide electric power which with quality is good the than facet sum up and also the quality. Others PT. PLN is also claimed to give professional service to customers or society. Along with that's writer has an eye to perform research with the title